The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations - Santos-Silva, Antonio; Nascimento, Francisco E. De L.; Kozlov, Anton Olegovich (Zootaxa, 2019)
Holonotus latithorax Thomson, 1861 (Prioninae, Solenopterini), and Periestola Breuning, 1943 (Lamiinae, Acanthocinini) are revalidated. A lectotype is designated for Holonotus latithorax. The following new synonyms are proposed: Lagocheirus plantaris indistinctus Dillon, 1957 = Lagocheirus plantaris plantaris Erichson, 1847 (Lamiinae, Acanthocinini); Paracobelura curiosa Monné & Martins, 1976 = Periestola strandi Breuning, 1943 (Lamiinae, Acanthocinini), with a new country record for Panama; Anisopodus humeralis Bates, 1863 = Anisopodus lignicola Bates, 1863, with a new Brazilian state record. New species are described from Colombia: Lepturges (Lepturges) brechlini; Pseudosparna antonkozlovi; Hyperplatys ushveridzei; Blabia antonkozlovi; and Cycnidolon antonkozlovi. The female of Nealcidion napoensis Nascimento & McClarin, 2018 is described, and the species is reported for Colombia for the first time. Additionally, the following new records are reported: Amniscites pictipes (Bates, 1863) from Colombia; two new department records in Colombia for Onalcidion tavakiliani Audureau, 2013; new department record in Colombia for Trypanidius irroratus Monné & Delfino, 1980; Icublabia multispinosa Galileo & Martins, 2003 for Colombia including additional notes; new department record in Colombia for Blabia intricata Martins & Galileo, 1995; Obrium costaricum Hovore & Chemsak, 1980 for Panama; Pantonyssus nigriceps Bates, 1870 for Colombia; Stizocera geniculata (Pascoe, 1866) for Colombia; and Pygmodeon obtusum (Bates, 1874) for Panama. Stizocera geniculata is also excluded from the fauna of the Brazilian state of Rondônia.